A qualitative investigation into millennial consumers’ willingness to pay higher prices for organically farmed products in Cape Town - Mandavela, Tchissola (The IIE, 2020)
An emergent concern for healthy food and sustainable agricultural production has resulted in increased attention towards organic food, and sustainable developments have to an extent contributed to organic premium prices subsequently, as organic food becomes more mainstream there is a rising demand for academic research on consumer habits and attitudes towards the same. Grounded on the Theory of Planned Behaviour (TPB) this study reviews and discusses why Millennial consumers in South Africa, Cape Town are willing to pay for goods that have been organically farmed even though they are susceptible to premium pricing which was explored through an interpretive investigation. Data was collected and generated using convenience sampling through semi-structured interviews with three participants who varied in terms of purchasing habits, race and age. The gathered data was then qualitatively evaluated through Thematic analysis. The seminal findings of this of the study indicated that health-conscious consumers display an increasing preference for organic food over conventionally grown food which is significantly influenced by factors such as; perceived quality, well-being and the rising incidence of diseases like cancer and diabetes. According to the study consumer perceptions, attitude and subjective norm greatly impact consumer’s intention to purchase organic food thus providing meaningful insights into contemporary researches of consumer behaviour towards organic food in South Africa.
Keywords: Consumer willingness; Prices; Millennials; Organically farmed products; Cape Town